2017
DOI: 10.1111/sjop.12417
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in treatment‐seeking OCD‐patients: Changes after concentrated exposure treatment

Abstract: Research indicates that patients with Obsessive Compulsive Disorder (OCD) frequently suffer from comorbid sleep difficulties, and that these difficulties often are not clinically recognized and diagnosed. There has been limited research investigating if comorbid sleep difficulties impair treatment outcome for OCD and if the sleep difficulties change following OCD-treatment. Thirty-six patients with obsessive compulsive disorder underwent concentrated exposure treatment delivered in a group over four consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(42 reference statements)
2
11
1
Order By: Relevance
“…This reflects a high rate of insomnia in the current group of patients and further add to the growing body of research indicating insomnia as a problem area for people with OCD ( 7 , 37 , 38 ). This finding is also in accordance with our previous finding of 70% insomnia in OCD ( 12 , 13 , 20 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This reflects a high rate of insomnia in the current group of patients and further add to the growing body of research indicating insomnia as a problem area for people with OCD ( 7 , 37 , 38 ). This finding is also in accordance with our previous finding of 70% insomnia in OCD ( 12 , 13 , 20 ).…”
Section: Discussionsupporting
confidence: 94%
“…In a previous effectiveness study ( 20 ), we explored whether concurrent self-reported insomnia in patients with OCD improved following the B4DT. There was a significant change in symptoms of insomnia from pre-treatment to 6-month follow-up, however residual symptoms were observed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations